Neurovascular mechanisms and blood–brain barrier disorder in Alzheimer’s disease - Bell, Robert D. (2009)
Vascular dysfunction has a critical role in Alzheimer’s disease (AD). Recent data from brain imaging studies in humans and animal models suggest that cerebrovascular dysfunction may precede cognitive decline and onset of neurodegenerative changes in AD and AD models. Cerebral hypoperfusion and impaired amyloid β-peptide (Aβ) clearance across the blood–brain barrier (BBB) may contribute to the onset and progression of dementia AD type. Decreased cerebral blood flow (CBF) negatively affects the synthesis of proteins required for memory and learning, and may eventually lead to neuritic injury and neuronal death. Impaired clearance of Aβ from the brain by the cells of the neurovascular unit may lead to its accumulation on blood vessels and in brain parenchyma. The accumulation of Aβ on the cerebral blood vessels, known as cerebral amyloid angiopathy (CAA), is associated with cognitive decline and is one of the hallmarks of AD pathology. CAA can severely disrupt the integrity of the blood vessel wall resulting in micro or macro intracerebral bleedings that exacerbates neurodegenerative process and inflammatory response and may lead to hemorrhagic stroke, respectively.Here, we review the role of the neurovascular unit and molecular mechanisms in vascular cells behind AD and CAA pathogenesis. First, we discuss apparent vascular changes, including the cerebral hypoperfusion and vascular degeneration that contribute to different stages of the disease process in AD individuals. We next discuss the role of the low-density lipoprotein receptor related protein-1 (LRP), a key Aβ clearance receptor at the BBB and along the cerebrovascular system, whose expression is suppressed early in AD. We also discuss how brain-derived apolipoprotein E isoforms may influence Aβ clearance across the BBB. We then review the role of two interacting transcription factors, myocardin and serum response factor, in cerebral vascular cells in controlling CBF responses and LRP-mediated Aβ clearance. Finally, we discuss the role of microglia and perivascular macrophages in Aβ clearance from the brain. The data reviewed here support an essential role of neurovascular and BBB mechanisms in contributing to both, onset and progression of AD.